Electrical and photoresponse properties of Au/reduced graphene:poly(3-hexylthiophene) nanocomposite/p-Si photodiodes - Wageh, S.; Al-Ghamdi, Ahmed A.; Al-Turki, Yusuf; Dere, Aysegul; Tjong, S. C.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2015)
Au/reduced graphene:poly(3-hexylthiophene) (P3HT) nanocomposite/p-Si/Al diodes have been prepared and their electrical characteristics have been investigated using current-voltage, capacitance-voltage and conductance-voltage measurements. The electronic parameters such as ideality factor (n) and barrier height ( were determined. The photocurrent of the diodes is higher than their dark current. This indicates that the diodes exhibited a photoconducting behavior under various illumination conditions. The diode having molar ratio of RG:P3HT 0.005 gives the highest photoresponsivity. This diode was analyzed in detail. The prepared Au/ RG:P3HT nanocomposite/p-Si/Al diode can be used as a solar position sensor for two axes tracking systems, a light meter, a sunlight detector and automatic shutter control sensor.
Keywords: Photodiode; Nanocomposite; Ideality factor